Utilization of Quizizz Learning Media in Teaching Vocabulary to Intermediate Level Bipa Learners - Nasution, Jamaluddin -; Siregar, Elfriati; Epriadi, Epriadi; Tumanggor, Evi Bunga; Amri, Hasanul (Universitas Harapan Medan, 2025)
This article was written with the aim of describing the use of quizizz learning media in teaching vocabulary to intermediate BIPA learners. The method used in the study is a qualitative and descriptive research method with a gamification learning method (Gamification Method). Data were collected through observation, test results, and questionnaires distributed to learners after the learning process. The process of utilizing quizizz learning media consists of three stages, namely the design or preparation stage, the implementation stage, and the evaluation stage. Based on the results of the learning evaluation carried out, it was found that the use of quizizz learning media in teaching vocabulary to intermediate BIPA learners was carried out well, which can be seen from the learning outcomes and points obtained during the quiz. This can also be seen from BIPA learners who have mastered vocabulary well and are able to write vocabulary into sentences. Therefore, it can be concluded that quizizz learning media is effective in teaching vocabulary to intermediate BIPA learners.